Sinonasal Lobular Capillary Hemangioma After Continuous Self-tests for COVID-19: A Case Report and Review of the Literature - Athanasios Luca FOUNTARLIS; Vasileios LACHANAS; Konstantina ZACHAROULI; Jiannis HAJIIOANNOU; Nikos KALOGRITSAS; Charalampos SKOULAKIS (Medeniyet Medical Journal)
Sinonasal lobular capillary hemangiomas (LCH) are rare benign vascular lesions commonly arising from the nasal septum. Nasopharyngeal, nasal mid-turbinate, and anterior nasal swabbing is the preferred method of screening for coronavirus disease-2019 (COVID-19). Herein, we present a case of a sinonasal LCH in a child after continuous self-tests for COVID-19, with an anterior nasal swab. The child presented with a well-defined red mass in the anterior part of the nasal septum, which was removed endoscopically. Histopathology revealed a LCH. This is the first report of a complication other than epistaxis with the use of an anterior nasal swab. Our literature review identified 32 studies reporting complications of COVID-19 screening. Cerebrospinal fluid leaks and foreign body retention are the most common ones. A proper specimen collection technique and a quick patient history with an emphasis on risk factors are the best practices to prevent complications from COVID-19 screening.